The Lean Production Educational Simulation Game - Cieśla, Maria; Bogacki, Adam (Management and Administration Journal, 2023)
The paper presents theoretical and practical analysis of the actual mapping mechanisms involved in the simulation game. In particular, the educational nature of real logistics processes modelling was emphasized. A secondary, but no less important aspect of reality as presented is attractive to buyers entertainment which helps receivers make the right decisions, known in the theory of assimilation issues. The presented simulation game is based on the creation of simple elements, which does not require additional knowledge and manual skills in this area from the participants. Suitably organizing jobs, reflecting the real production cells helps to understand the essence of the production control support tools based on Lean Production, pointing out the differences between conventional work cells,and the push and pull system.